2020
DOI: 10.1038/s41467-020-17937-4
|View full text |Cite
|
Sign up to set email alerts
|

Life histories determine divergent population trends for fishes under climate warming

Abstract: Most marine fish species express life-history changes across temperature gradients, such as faster growth, earlier maturation, and higher mortality at higher temperature. However, such climate-driven effects on life histories and population dynamics remain unassessed for most fishes. For 332 Indo-Pacific fishes, we show positive effects of temperature on body growth (but with decreasing asymptotic length), reproductive rates (including earlier age-atmaturation), and natural mortality for all species, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 50 publications
(74 reference statements)
3
36
2
Order By: Relevance
“…Negative correlations between maximum size, asymptotic size, or size‐at‐age of old fish, and temperature have been found in commercially exploited fish species (Baudron et al, 2014; Ikpewe et al, 2020; van Rijn et al, 2017). However, other studies, including large‐scale experiments, controlled experiments and latitudinal studies, or observational data on unexploited species, have found no or less clear negative relationships between maximum size, growth of old fish, or mean size and temperature (Audzijonyte et al, 2020; Barneche et al, 2019; Denderen et al, 2020; van Dorst et al, 2019; Huss et al, 2019) and differences between species may be related to life‐history traits and depend on local environmental conditions (Denderen et al, 2020; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Negative correlations between maximum size, asymptotic size, or size‐at‐age of old fish, and temperature have been found in commercially exploited fish species (Baudron et al, 2014; Ikpewe et al, 2020; van Rijn et al, 2017). However, other studies, including large‐scale experiments, controlled experiments and latitudinal studies, or observational data on unexploited species, have found no or less clear negative relationships between maximum size, growth of old fish, or mean size and temperature (Audzijonyte et al, 2020; Barneche et al, 2019; Denderen et al, 2020; van Dorst et al, 2019; Huss et al, 2019) and differences between species may be related to life‐history traits and depend on local environmental conditions (Denderen et al, 2020; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Negative correlations between maximum size, asymptotic size or size-at-age of old fish and temperature have been found in commercially exploited fish species (Baudron et al, 2014;Ikpewe et al, 2020;van Rijn et al, 2017). However, other studies, including large scale experiments, controlled experiments and latitudinal studies or observational data on unexploited species, have found no or less clear negative relationships between maximum size, growth of old fish or mean size and temperature (Audzijonyte et al, 2020;Barneche et al, 2019;Denderen et al, 2020;Huss et al, 2019;van Dorst et al, 2019) and differences between species may be related to life history traits and depend on local environmental conditions (Denderen et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, organisms' life history traits represent how variable the environmental changes are in their habitat (Hovel et al, 2017;Chaparro-Pedraza and de Roos, 2019). Consequently, changes in the species geographic distribution and its realized niche induced by climate variability can impact these traits (de Roos and Persson, 2013;Wang et al, 2020;Chaudhary et al, 2021). For example, the reproductive strategies of the majority of species depend on environmental conditions (e.g., temperature, salinity, light:dark cycles, and food availability).…”
Section: Life History Traitsmentioning
confidence: 99%
“…The effects of climate change can also affect species differentially based on their lifespan and generation time. For example, in comparison to taxa with short-generation times (benthopelagic and reef fishes; up to 5 years), accelerated development and life histories due to global warming can lead to lower mortality and higher fecundity earlier in life in taxa with long-generation times (elasmobranch, bathydemersal, demersal; over 10 years) (Wang et al, 2020). In addition, simulation models suggest that species that possess long lifespans, relative to the change in environmental conditions, may be more plastic in comparison to species with short lifespan (Ratikainien and Kokkoo, 2020).…”
Section: Life History Traitsmentioning
confidence: 99%